The Chester Beatty Papyrus and the Caesarean Text of John - Tasker, R. V. G. (Harvard theological review, 1937)
In the Journal of Theological Studies for October 1935 I discussed certain of the more interesting readings of the Chester Beatty Papyrus in John on general grounds, endeavouring to discover how far the evidence of the papyrus might reasonably be allowed to modify the conclusions of particular editors in particular passages. It became obvious in that study that the text of the papyrus in John does not belong specifically to any of the recognised groupings, and that in many cases it would appear not to have retained the reading which is intrinsically probable, or which is the best attested.